AIRXORCIST : RAISING AWARENESS ABOUT AIR POLLUTION THROUGH COMPUTER GAME - Fan, Jian Wei (Universiti Malaysia Sarawak (UNIMAS), 2019)
Air pollution is a serious problem that requires people’s attention. There is a need to raise awareness about air pollution among people. In order to do so, an edutainment computer game is one plausible method. An online survey is conducted among public members to study the level of awareness on air pollution and general opinions on computer game. From the survey result, there are incorrect knowledge about air pollution detected among the participants, and some of the participants are not aware that they are directly contributing to air pollution due to the incorrect knowledges. The result also revealed that there is a demand for RPG educative games among the participants. Thus, an edutaining RPG computer game entitled “AirXorcist” is developed using Unity to help raise awareness about air pollution. A final testing, which involves a pre-game test and a post-game test, is also carried out among randomly selected public members to determine whether “AirXorcist” is able to help in raising awareness about air pollution.